The Welfare State and Gender Equality - Evelyne Huber; John D. Stephens; David Bradley; Stephanie Moller; François Nielsen (Luxembourg Income Study (LIS), 2001)
This paper examines the determinants of several indicators of economic well being of women. The feminist literature has suggested that women's well being is best measured through both the economic status of women and power relations vis-à-vis men. Barbara Hobson has proposed that the percentage of single mothers in poverty and married women's income as a proportion of both spouses' income effectively measure economic status and power relations. The dependent variables are calculated from micro data available in the Luxembourg Income Survey (LIS) archive, which now contains enough countries and time points to allow multivariate statistical analysis with a sufficiently large number of independent variables to test a broad range of hypotheses on the determinants of gender egalitarian outcomes while controlling for other possible determinants. In the case of poverty among single mothers, the LIS data also allow us to go beyond Hobson's single indicator to investigate the extent to which government action is responsible for poverty reduction. Hence, we analyze 4 dependent variables: 1) pre tax and transfer poverty rates among single mothers, 2) reductions in single mothers' poverty due to taxes and transfers, 3) post tax and transfer poverty rates among single mothers, and 4) women's wages relative to spouses' wages. In these analyses, we test feminist theories along with theories of economic structure, labor market institutions, state structure and political power.
Keywords: 330; Sozialstaat; Industrieländer; Geschlechterdiskriminierung